Kajian Keamanan Pangan: Analisis Methanyl Yellow Dan Formalin Pada Makanan Jajanan Di SDN Rappokalling - Farihah Muhsanah; Hasriwiani Habo Abbas; Ulfa Sulaeman; Dwi Adelia (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Food safety of school snacks is an important issue because elementary school children are considered a vulnerable group to exposure to hazardous chemical substances. Emphasizing this can help school administrators, health officials, and policymakers feel a shared responsibility to protect students' health and motivate action. The results showed that 30% of dry snacks tested positive for Methanyl Yellow, while 30% of wet snacks tested positive for formaldehyde. Overall, 60% of the snacks contained at least one hazardous substance and were categorized as unsafe, whereas only 40% were classified as safe. This highlights the need for combined efforts from all stakeholders to reduce health risks and improve snack safety. In conclusion, most school snacks at SDN Rappokalling did not meet food safety standards and may pose health risks to students. Recognizing this, school administrators, food vendors, and policymakers can feel empowered to implement effective supervision, education, and policy measures to improve safety.